تمثل الأنا الآخر في رحلة مبارك الميلي إلى فيشي - بن لباد, رفيقة (جامعة الوادي - university of Eloued, 2022)
قرأنا عن أدب الرحلة الذي يعد حقلا خصبا في كتب الأدب و التاريخ و الذي عرفه الغرب و العرب منذ القدم. ومن هذا المنطلق يمكن لنا أن تعتبر أن كتب الرحلات من أهم المصادر. حيث أن الباحث يجد ظالته من مشاهد واقعية. وهذا ما جعل التاريخ حافلا بأسماء العديد من أعلام أدب الرحلة، الذين ارتحلوا و زاروا و شاهدوا و دونوا. و الجزائر واحدة ممّن يفتخر بعلمائها في هذا الفن، وخرج من أرضها رحالة صالوا وجالوا كثيرا، ودونوا انطباعاتهم وملاحظاتهم وقصصهم، والتعريف بأعلامها البارزين إلى غير ذلك من الأمور المهمة التي تستدعي الذكر. ومن هؤلاء الرحالة نجد مبارك الميلي و زيارته إلى فيشي ونظرته للمدينة و أصحابها ومقارنته بين فيشي و ميلة. . Abstract: We read about travel literature, which is a fertile field in literature and history books that the West and Arabs have known since ancient times. In this sense, we can consider travel books as one of the most important sources. Where the researcher finds shadows from realistic scenes. This is what made history full of the names of many famous travel writers, who traveled, visited, witnessed and wrote down. And Algeria is one of those who are proud of its scholars in this art. Travelers who prayed and toured a lot came out of its land, writing down their impressions, observations and stories, and introducing its prominent figures to other important matters that require mention. Among these travelers, we find Mubarak Al-Maili and his visit to Vichy.
مقال
Keywords: دب، الرحلة، أسلوب السرد،مبارك الميلي، الأنا و الآخر; iterature, the journey, narration style, Mubarak Al-Maili, the ego and the other